Penyuluhan Sistem Keamanan Pangan Dalam Produksi Keripik Tempe Di Desa Parerejo Kabupaten Jawa Timur - Nurani, Fesdila Putri; Kurniati, Ely (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
Food Safety sistem is a method that commonly use to guarantee the quality of food product in order to avoid hazard which can causing harm to the consumer. One of the well-known traditional food, Tempe, which is made from fermented soybean, has consumed by most of people in Indonesia. Tempe has a short shelf life. The aim of processing Tempe are to make the shelf life longer and also to diversify product of Tempe. One of the most popular product of Tempe is Tempe cracker. Parerejo village is well-known as one of the Tempe and Tempe cracker production base in East Java. Unfortunately, its production has not yet applied Food Safety Sistem. Some actions were needed in order to improve the knowledge of the Tempe and Tempe cracker producers about Food Safety Sistem. Firstly, questionnaires were distributed to the Tempe and Tempe Cracker producers in Parerejo village to determine the level of community understanding about Food Safety Sistem. After distributing the questionnaires, the next action was presenting of the definition, the aspects and the importance of implementation Food Safety Sistem in the production process of Tempe and Tempe cracker. Questionnaires showed that most of the producers of Tempe and Tempe crackers in Parerejo village realizes the importance of implementation Food Safety Sistem. In other hand, Food Safety Sistem has some obstacles to fully apply in the production process. The biggest challenge is the production facilities. Improving sanitation sistems such as sanitation of workers and equipment is one of the real efforts that can be done to improve the production sistem. Sortation of raw material also an effort to avoid physical hazard that can causing harm of the product. At least, awareness of the community about Food Safety Sistem have improved and committed to do some correction in order to avoid the hazard in production process.